Decision Support System for Selection of Outstanding Students at the Faculty of Mathematics in Natural Sciences at the University of Yogyakarta with AHP and TOPSIS Methods - Aan Yulianto (Institute of Computer Science (IOCS), 2021)
Yogyakarta State University (UNY) annually holds the selection of outstanding students for the Bachelor (S1) program, namely students who have achieved high achievements, both curricular, co-curricular, and extra-curricular according to the specified criteria. To assist in determining the winners of outstanding students, a Decision Support System (SPK) is needed that is able to provide alternative solutions. The method used in the SPK for the Selection of Outstanding Students uses the Analytical Hierarchy Process (AHP) for weighting the criteria and the Technique For Order Preference by Similarity to Ideal Solution (TOPSIS) to find the winning solution. The design of the SPK for the Selection of Outstanding Students uses the Waterfall model. The output of the system is presented in the form of calculation results of AHP and TOPSIS which can be considered further by decision makers. SPK is built based on a website designed using Sublime software (text editor), Database Management System (DBMS) MySQL Xampp 7 and PHP programming language. The DSS is tested on users and experts. Based on the test, the results show that Correctness is included in very good criteria, Reliability is included in very good criteria, Integrity is included in very good criteria, Usability is included in good criteria, meaning that SPK can meet user needs, such as assisting the registration process, judging and processing data for election participants the most oustanding student. SPK can display information according to user input correctly. Instructions for using DSS help users. SPK is safe from unauthorized parties. The appearance of the SPK is attractive and easy to use.